Identifying HIV care enrollees at-risk for cannabis use disorder. Issue 7 (3rd July 2017) - Hartzler, Bryan; Carlini, Beatriz H.; Newville, Howard; Crane, Heidi M.; Eron, Joseph J.; Geng, Elvin H.; Mathews, W. Christopher; Mayer, Kenneth H.; Moore, Richard D.; Mugavero, Michael J.; Napravnik, Sonia; Rodriguez, Benigno; et al.
ABSTRACT: Increased scientific attention given to cannabis in the United States has particular relevance for its domestic HIV care population, given that evidence exists for both cannabis as a therapeutic agent and cannabis use disorder (CUD) as a barrier to antiretroviral medication adherence. It is critical to identify relative risk for CUD among demographic subgroups of HIV patients, as this will inform detection and intervention efforts. A Center For AIDS Research Network of Integrated Clinical Systems cohort ( N  = 10, 652) of HIV-positive adults linked to care at seven United State sites was examined for this purpose. Based on a patient-report instrument with validated diagnostic threshold for CUD, the prevalence of recent cannabis use and corresponding conditional probabilities for CUD were calculated for the aggregate sample and demographic subgroups. Generalized estimating equations then tested models directly examining patient demographic indices as predictors of CUD, while controlling for history and geography. Conditional probability of CUD among cannabis-using patients was 49%, with the highest conditional probabilities among demographic subgroups of young adults and those with non-specified sexual orientation (67–69%) and the lowest conditional probability among females and those 50+ years of age (42% apiece). Similarly, youthful age and male gender emerged as robust multivariate model predictors of CUD. In the context of increasingly lenient policies for use of cannabis as a therapeutic agent for chronic conditions like HIV/AIDS, current study findings offer needed direction in terms of specifying targeted patient groups in HIV care on whom resources for enhanced surveillance and intervention efforts will be most impactful.